2013
DOI: 10.1089/ars.2012.5136
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide and Nitric Oxide: Key Regulators of the Legume—Rhizobiumand Mycorrhizal Symbioses

Abstract: A challenging question is to define more precisely when and where reactive species are generated and to develop adapted tools to detect their production in vivo. To investigate the role of Noxs and NRs in the production of H(2)O(2) and NO, respectively, the use of mutants under the control of organ-specific promoters will be of crucial interest. The balance between ROS and NO production appears to be a key point to understand the redox regulation of symbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(138 citation statements)
references
References 155 publications
1
134
0
3
Order By: Relevance
“…These results confirmed that AM symbiosis was able to provide specific adaptation mechanisms to the host plant to tolerate long-term K + deprivation. ROS have been detected in legume roots colonized by both AM fungi and nitrogen-fixing bacteria, particularly in colonized cells (Salzer et al, 1999;Fester and Hause, 2005;Puppo et al, 2013). Moreover, some NADPH oxidase-encoding genes were recently found to be up-regulated in colonized cortical cells of M. truncatula roots, suggesting their role in arbuscule development (Belmondo et al, 2016a(Belmondo et al, , 2016b.…”
Section: Am Symbiosis Modulates the Plant Responses To K + Deprivationmentioning
confidence: 99%
“…These results confirmed that AM symbiosis was able to provide specific adaptation mechanisms to the host plant to tolerate long-term K + deprivation. ROS have been detected in legume roots colonized by both AM fungi and nitrogen-fixing bacteria, particularly in colonized cells (Salzer et al, 1999;Fester and Hause, 2005;Puppo et al, 2013). Moreover, some NADPH oxidase-encoding genes were recently found to be up-regulated in colonized cortical cells of M. truncatula roots, suggesting their role in arbuscule development (Belmondo et al, 2016a(Belmondo et al, , 2016b.…”
Section: Am Symbiosis Modulates the Plant Responses To K + Deprivationmentioning
confidence: 99%
“…The establishment of the symbiosis is highly specific, as a rhizobia species will only interact with a specific legume species. Specificity is greatly influenced by the Nod signalling pathway [30], but H 2 O 2 and † NO also play a role in the proximal mechanisms associated with the specific establishment of the symbiosis [31]. Indeed, in the common bean Phaseolus vulgaris, the contact of roots with NF rapidly triggers a transient burst of intracellular ROS at the tip of the hairs [32].…”
Section: Pleiotropic Roles Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…From the bacterial point of view, transgenic S. meliloti unable to scavenge † NO are less competitive than wild-type rhizobia in the nodulation process [37], suggesting that † NO is necessary for an optimal establishment of the association. Similar to the squid-vibrio symbiosis [27], it has been proposed that the initial exposure to † NO primes the symbionts to resist against stressful conditions encountered during later symbiotic stages [31].…”
Section: Pleiotropic Roles Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…Then, in 1979, Keppler (1979) reported that plants treated with different herbicides can generate NO [7]. However during the 1990s, NO research was extended to plant cells, this molecule being involved in a wide spectrum of functions during plant growth and development, as well as in the mechanism of interaction with beneficial microorganisms, defenses against pathogens, and adverse environmental stresses [8][9][10][11]. The main goal of this work is to provide a brief overview of the relevance of NO and derived molecules designated as reactive nitrogen species (RNS) in higher plants.…”
Section: A Short Historical Perspective About Nomentioning
confidence: 99%